Interdisciplinary postdoctoral training in global health through a novel joint project for trainees from diverse disciplines: Benefits, risks, and observations - Oberhelman, Richard A. (2017)
Postdoctoral training programs are usually highly individualized arrangements between trainees and a limited number of senior mentors in their field, an approach that contrasts with current trends in public health education that promote interdisciplinary training to spur innovation. Herein, we describe an alternative model for postdoctoral training for a group of fellows from distinct disciplines. Fellows work with mentors from diverse fields to create a joint research project or a group of complementary projects, with the goal of developing a new device, intervention, or innovation to address a global health problem. The perceived benefits, challenges, and limitations of this team approach to interdisciplinary postdoctoral training are presented.